Yashawantrao chaven : selected speeches in the state legilsature 1946-1962 ( Marathi) - Khobrekar, V.G (Mumbai Yashwantrao Chanvan Pratishthan, 2012)
Maharashtra has always produced statesmen, warriors, scientists, literateurs that have distinguished themselves not only in their native Maharashtra but in the whole of India. The Great Shivaji of course comes to the mind of every true Maharashtrian. In fact, despite the attempts of his detractors to denigrate his image, Shivaji was, it has been established, a warrior of the stature of Alexander the Great. There have been hundreds of others in different fields. The late Shri Y. B. Chavan, was one of such national leader, who transcended the borders of Maharashtra. The famous poet, the late Shri Shripad Krishna Kolhatkar, has described this trait of Maharashtrians in his famous poem on Maharashtra in the following words, Deekeâeb#eeheg{efle efpeLes ieieve "WieCes (the sky is the limit for the ambitious). It would be no exaggeration here to assert that Shri Y. B. Chavan was one of the very few leaders in Maharashtra, who could easily be included in the galaxy of the political luminaries like Dadabhai Naoroji, Mahadev Govind Ranade, Gopalkrishna Gokhale and Bal Gangadhar Tilak. But, the personality of Shri Y. B. Chavan differed from the above giants of Indian politics, inasmuch as that his roots were in rural ambient of Maharashtra where he familiarised himself with the conditions of the toiling masses and hardworking peasantry who form the backbone of this country. This rural background stood him in good stead in his career in adopting a realistic and down-to-earth approach to problems facing him. After an apprenticeship as a freedom-fighter, during the forties and a couple of jail terms, Shri Chavan was rather hesitant about the future course of action. In the jail he was introduced to the writin
Keywords: Biography